ANALISA FLAVONOID DARI EKSTRAK ETANOL 96% KULIT BUAH OKRA MERAH (Abelmoschus esculentus L. Moench) SECARA KROMATOGRAFI LAPIS TIPIS DAN SPEKTROFOTOMETRI UV-VIS - Nia Lisnawati; Indri Astuti Handayani; Ni'matul Fajrianti (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2016)
Has done research on flavonoids Analysis of Ethanol Extract 96% Fruit Leather Red Okra In Thin Layer Chromatography and Spectrophotometer UV-Vis. The purpose of this study was to analyze the content of the fruit skin red okra (Abelmoschus esculentus L. Moench) by using the method of thin layer chromatography (TLC) under UV light and spectrophotometry UV-Vis. Reference standards used in this study is the Standard Solution Routine Quercetin. The results of the research that has been done by the method of thin layer chromatography obtained Rf values of 0.81 and produces the color orange. And the results of research conducted by spectrophotometry UV-Vis method obtained 333,117 mg.L-1 or 421,629 mg.kg-1 or 0,84339 %. The conclusion from this study is that the 96% ethanol extract of the fruit leather red okra (Abelmoschus esculentus L. Moench) positive (+) contains flavonoids with levels of 0,84339 %.